Numerical study on the effect of angle of inclination on magnetoconvection inside enclosure with heat generating solid body - Umadevi, P.; Nithyadevi, N.; Öztop, Hakan Fehmi (Informatics Publishing Limited and The Indian Mathematical Society, 2019)
Convective flow and heat transfer of fluid inside a square enclosure having heat generating solid body, with various thermal boundary conditions is investigated numerically. The top wall of the enclosure is adiabatic, both the bottom and right walls are kept at constant temperature, while the left wall is heated using sin function. Numerical simulations is carried out by solving the governing equations using SIMPLE algorithm by means of the finite-volume method with power-law scheme. The important parameters focused are angle of inclination of the enclosure, area ratio of solid-enclosure, Hartmann number and temperature difference ratio of solid-fluid, which are ranges 0o - 90o, 0.0625 - 0.5625, 0 - 100 and 0 - 50, respectively. Thermal conductivity ratio of solid-fluid is fixed as 5 and Rayleigh number as 105 © Indian Mathematical Society, 2019.
Keywords: Angle of Inclination; Convection; Finite Volume Method; Hartmann Number; Sinusoidal Heating